Energy-efficient retrofitting with exterior shading device in hot and humid climate – case studies from fully glazed multi-storied office buildings in Chennai, India - Chandrasekaran C; Kumudhavalli Sasidhar; A. Madhumathi (Journal of Asian Architecture and Building Engineering, 2023)
Many existing buildings are not sustainable, such as poorly insulated office buildings with large glass window panels that significantly increase the cooling energy use in a hot and humid climate. Energy-efficient retrofitting can substantially reduce energy use through a passive façade design. This paper suggests simulation as a method for selecting a façade retrofit solution at the early design stage. A façade retrofit solution that requires the integration of all three sustainability dimensions: energy efficiency, visual comfort, and economics. Two case studies of fully glazed multi-storied office buildings of different sizes demonstrate the methodology. This research adopted two simulation methods: one for façade retrofit solutions with fixed exterior shading device (ESD) types and the other for a dynamic ESD. The results show that fixed ESD with perforated fabric for 100% of the glazing area was 22.7% energy-saving retrofitting solution than the base case for the small sample and 17% energy-saving for the large sample with a low payback period of 7 years for both the case sample. Building practitioners, stakeholders, and end-users can use this simulation methodology for a successful façade retrofit decision-making at the early design stage.